2016
DOI: 10.3892/ijo.2016.3600
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin inhibits EGF-induced JB6 cell transformation by targeting PI3K

Abstract: Phosphatidylinositol 3-kinases (PI3Ks) are lipid kinases that play fundamental roles in regulation of multiple signaling pathways, including cell proliferation, survival and cell cycle. Increasing evidence has shown that abnormal activation of PI3K pathway contributes to tumorigenesis and progression of various malignant tumors. Therefore, it is an attractive target of chemoprevention and chemotherapy. Eupatilin, a natural flavone compound extracted from Artemisia vulgaris, has antitumor and anti-inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This is in line with the diverse therapeutic function of eupatilin in various diseases through transinteraction. Another study also suggests that eupatilin targets the AKT signaling pathway in cancer cells, causing cell cycle arrest [27]. Treatment with eupatilin in the xenograft mouse model for esophageal cancer inhibits the activity of AKT and ERK1/2 in tissues [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the diverse therapeutic function of eupatilin in various diseases through transinteraction. Another study also suggests that eupatilin targets the AKT signaling pathway in cancer cells, causing cell cycle arrest [27]. Treatment with eupatilin in the xenograft mouse model for esophageal cancer inhibits the activity of AKT and ERK1/2 in tissues [9].…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). Our previous study demonstrated that eupatilin induced cell cycle arrest at the G 0 /G 1 phase by inhibiting the activity of cyclin D1 in EGF-treated JB6 cells (24). However, G 2 /M arrest of the cell cycle has been observed in eupatilin-treated human endometrial carcinoma Hec1A cells (37).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, there is an urgent need to identify more useful methods that can prevent or treat the malignant cancer. Eupatilin, a flavone compound, has potential anticancer activity (6,24). It has been reported that eupatilin induces human renal cancer cell apoptosis via ROS-mediated MAPK and PI3K/AKT signaling pathways (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation